Construction and demolition waste: a review of uses and applicability on roads and highways (2015 – 2020) (Research, Society and Development, 2021)
The understanding of the state of the art in relation to the application of construction and demolition waste (CDW) is intended to deepen the knowledge on the subject, which has gained importance given its great representation among urban solid waste (USW), contributing to environmental pollution, while approaching 50% of the constitution of all MSW in large Brazilian cities and can also reach this value in world cities. Thus, it is essential to know the various existing methods of using CDW in order to benefit the environment, as well as the economy and society, which are the three pillars of sustainable development. Thus, a systematic literature review (SLR) was developed in two databases, Web of Science and Science Direct, where articles were extracted between the years 2015 and 2020, with key words listed according to the theme. Resulting in 5 different types of subjects addressing CDW, starting with an overview of Construction and Demolition Waste to reuse possibilities for the various types of CDW produced in cities worldwide.